2010
DOI: 10.1371/journal.pone.0009343
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Genetic Instability in Tumors and Normal Nearby Tissues

Abstract: BackgroundComprehensive analyses have recently been performed on many human cancer tissues, leading to the identification of a number of mutated genes but providing no information on the variety of mutations present in each of them. This information is of interest to understand the possible origin of gene mutations that cause tumors.Methodology/Principal FindingsWe have analyzed the sequence heterogeneity of the transcripts of the human HPRT and G6PD single copy genes that are not considered tumor markers. Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This enhanced enzyme activity coincides with an increased ratio of the pentose monophosphate to the hexose monophosphate pool during late G1 and S phases of cell cycle, suggesting a potential role for pentose phosphates in proliferation signalling. Geraci et al (2010) detected genetic heterogeneity among G-6-PD transcripts in colon and colorectal tumours. In case of S. mansoni infection, G-6-PD was significantly increased (Shaheen et al.…”
Section: Resultsmentioning
confidence: 91%
“…This enhanced enzyme activity coincides with an increased ratio of the pentose monophosphate to the hexose monophosphate pool during late G1 and S phases of cell cycle, suggesting a potential role for pentose phosphates in proliferation signalling. Geraci et al (2010) detected genetic heterogeneity among G-6-PD transcripts in colon and colorectal tumours. In case of S. mansoni infection, G-6-PD was significantly increased (Shaheen et al.…”
Section: Resultsmentioning
confidence: 91%
“…In this study, we avoided this possible drawback by also sequencing matching normal breast and blood samples, and found that AR genetic heterogeneity was also present in both of these tissues. Interestingly, a study examining colorectal cancer tissues also found genetic heterogeneity in nearby healthy tissues [Geraci et al, ].…”
Section: Discussionmentioning
confidence: 99%